America or India: Identifying a Suitable Off-Grid Rural Electrification Model for Nigeria. - Herbert, Eti Best (Journal of Sustainable Development Law and Policy, 2025)
Most Nigerian living in the rural areas lack access to electricity due to lack of connectivity to the national grid network. The national grid expansion strategy to rural areas has not yielded much result due to financing and centralised approach. Off-grid electricity is considered more suitable for rapid electrification of rural areas. This paper examined the American and Indian approach to rural electrification and derived suitable lessons for Nigeria. While America ensured a robust national grid network to service rural areas, India adopted the renewable energy based off-grid options, thereby becoming the fastest developing country in rural electrification.